2018
DOI: 10.2174/0929867324666170911162331
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Antimalarials in Interferonopathies: New Perspectives for Old Drugs

Abstract: The story of antimalarials as antinflammatory drugs dates back few centuries. Chinin, the extract of the Cinchona bark, has been exploited since the 18th century for its antimalarial and antifebrile properties. Later, during the Second World War, the broad use of antimalarials allowed arguing their antirheumatic effect on soldiers. Since then, these drugs have been broadly used to treat Systemic Lupus Erythematosus, but, only recently, the molecular mechanisms of action have been partly clarified.The inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Quinacrine (QC), a previously identified inhibitor of the cGAS-STING pathway, was included in this study as a control. Consistent with the findings of a previous study (An et al, 2015;Piscianz et al, 2018), QC showed similar IC 50 values in MEFs and IMR-90 cells (6.36 ± 5.80 and 12.18 ± 1.52 mM, respectively). Moreover, astin C did not affect the expression of Il6 mRNA induced upon treatment with TLR agonists poly(I:C) (added into culture medium), lipopolysaccharide (LPS), or R837 ( Figure S1E).…”
Section: Astin C Specifically Inhibits Cytosolic Dna-trigged Gene Expsupporting
confidence: 92%
See 1 more Smart Citation
“…Quinacrine (QC), a previously identified inhibitor of the cGAS-STING pathway, was included in this study as a control. Consistent with the findings of a previous study (An et al, 2015;Piscianz et al, 2018), QC showed similar IC 50 values in MEFs and IMR-90 cells (6.36 ± 5.80 and 12.18 ± 1.52 mM, respectively). Moreover, astin C did not affect the expression of Il6 mRNA induced upon treatment with TLR agonists poly(I:C) (added into culture medium), lipopolysaccharide (LPS), or R837 ( Figure S1E).…”
Section: Astin C Specifically Inhibits Cytosolic Dna-trigged Gene Expsupporting
confidence: 92%
“…*p < 0.05 and **p < 0.01. See also Figures S1-S3 and Table S1. to attenuate cGAS activity and have been applied to improve the treatment of type I interferonopathies (An et al, 2015;Piscianz et al, 2018). In addition, H151 was recently characterized as a potent and covalent small-molecular inhibitor of STING (Haag et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, drugs acting on the IFN pathway are increasingly used for interferonopathies treatment [48,49]. The more listed are antimalarials, old drugs acting on the sensing of nucleic acids in lysosomes and, according to recent findings, on the activation of cGAS enzyme, the principal inducer of type I IFN signalling [50].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RU.521, PF-06928215 and suramin were found to be high-affinity inhibitors of cGAS [149,150]. Interestingly, a few antimalarial drugs, including quinacrine and chloroquine, were also reported to dismiss the activity of cGAS [151,152]. Moreover, disrupting the degradation and expression of STING may provide new insight into the development of small molecular modulators of STING activity.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%